The Bahá'í Faith and the Equality, Rights, and Advancement of Women: A Survey of Principles, Praxis, and Discourse - Momen, Wendi (Religions, 2023)
This article examines the Bahá’í approach to the equality of women and men, the education, advancement, and rights of women and girls; their application within the Bahá’í community; and the efforts of the Bahá’ís to influence the international discourse on women. Focusing on significant and interrelated social issues—the education of girls; leadership and participation in decision-making, and violence against women and girls—the article explores these through Bahá’í texts, accounts, and examples of how these have been operationalized by Bahá’í institutions, communities, and individuals; individuals; and in public statements made by Bahá’í institutions.